Epitaxial-strain–dependent reorientation of oxygen octahedral tilting axis in manganite films. (1st February 2022) - Zhang, Wujun; Jin, Feng; Zhang, Xingchang; Tang, Yuling; Xu, Pan; Lin, Nan; Wang, Zuyong; Wu, Wenbin; Ma, Chao
Abstract: As one of the most ubiquitous lattice distortions in complex transition metal oxides, oxygen octahedral rotation/tilting plays an important role in their physical properties. In this paper, we report the evolution of oxygen octahedral tilting in La2/3 Ca1/3 MnO3 films grown on NdGaO3 substrates with different orientations by using an aberration-corrected scanning transmission electron microscope. Different epitaxial strains depending on the substrate orientation lead to different orientation relationships between the films and substrates. Unlike conventional coherent growth, our experimental results demonstrate that the reorientation of the oxygen octahedral tilting axis, depending on epitaxial strains, would occur at the interface between the film and substrate for the (010)-oriented substrate or inside the film for the (1-12)-oriented substrate, as well supported by theoretical calculations via density functional theory method and electron energy loss spectroscopy measurements. Considering the universality of interfacial oxygen octahedral coupling in oxide heterostructures, these experimental findings offer great insights in understanding thickness- and orientation-dependent physical properties of thin films.